Radiopharmaceuticals for Positron Emission Tomography in Dementia Diagnosis - Ajdinović, Veljko; Ajdinović, Boris (British Journal of Healthcare and Medical Research, 2025)
Positron emission tomography (PET) is a method of nuclear medical imaging which, using molecules traced by the positron radionuclides (radiopharmaceuticals), allows insight into the metabolic processes in the body. Introducing new radiopharmaceuticals, the range of possibilities that PET can offer not only in oncology, but also in cardiology, neurology, and psychiatry was expanded. The aim of this paper is to present the new PET radiopharmaceuticals in dementia diagnostics. Dementia represents an acquired and persistent disorder of intellectual functions with a deficit in at least three of the following intellectual functions: memory, language, visuospatial abilities, personality and behavior, and other cognitive abilities, such as abstract thinking, computing, reasoning, and planning. Radiopharmaceuticals used in research and diagnosis of patients suffering from dementia are divided according to the target they are supposed to visualize into radiopharmaceuticals for: representation of the energetic metabolism of the brain (glucose/hexokinase transport), visualization of the incorrectly configured proteins (β-amyloid plaques, tau, α-synuclein), representation of the neurotransmitter systems, representation of the synaptic density (synaptic vesicle glycoprotein 2A (SV2A) labeled), and representation of the neuroinflammation. Studies with the PET radiopharmaceuticals for the new pathophysiological processes can result in earlier diagnosis and better classification of the neurodegenerative disorders, as well as in choosing appropriate therapeutic procedure for each individual patient and in improved monitoring of the effects of therapy.